Gelatin‐Assisted Synthesis of Vaterite Nanoparticles with Higher Surface Area and Porosity as Anticancer Drug Containers In Vitro. Issue 2 (24th November 2015) - Wang, Anhe; Yang, Yang; Zhang, Xiaoming; Liu, Xingcen; Cui, Wei; Li, Junbai
Abstract: The fabrication of porous vaterite nanoparticles with improved stability in aqueous solution and higher surface area is still a challenge. Here, inspired by the formation of mesoporous silica nanoparticles, we have taken gelatin as a "surfactant" to assist in the formation of vaterite nanoparticles and help create pores on their surface due to the distinct solubility and molecular morphology of gelatin in different solutions. The formation mechanism of vaterite nanoparticles and pores was investigated in detail, indicating that the existence of gelatin has a crucial effect on the formation of vaterite nanoparticles and their stability. Meanwhile, the elution of gelatin from vaterite nanoparticles via washing with hot water accounts for their higher surface area. Their application as an anticancer drug (doxorubicin) carrier after folic acid treatment was also investigated. These nanoparticles have advantages for drug release due to their pH‐sensitive structure and also have enhanced cytotoxicity toward cancer cells due to the folic acid modification. Abstract : Holey vaterite nanoparticles ! Porous vaterite nanoparticles (VNs) fabricated with gelatin assistance displayed high surface area and improved stability in aqueous solution. Their application as doxorubicin containers and their therapeutic efficacy against cancer cells were investigated in vitro. The vaterite nanoparticles prove to be excellent containers for anticancer drugs after modification by folic acid.